Immune Checkpoint Inhibitor-Induced Central Diabetes Insipidus: Looking for the Needle in the Haystack or a Very Rare Side-Effect to Promptly Diagnose? - Barnabei, Agnese; Strigari, Lidia; Corsello, Andrea; Paragliola, Rosa Maria; Falzone, Luca; Salvatori, Roberto; Corsello, Salvatore Maria; Torino, Francesco (Frontiers in Oncology, 2022)
Immune checkpoint inhibitors (ICIs) have improved the survival in patients affected by an increasing number of malignancies, but they may also trigger various autoimmune side-effects, including endocrinopathies. Very rarely, ICIs have been reported to cause central diabetes insipidus (CDI). However, with their expanding use, the likelihood that oncologists will be faced with CDI induced by ICIs (ICI-CDI) is expected to increase. By reviewing the limited literature on ICI-CDI, some inconsistencies emerge in both the diagnosis and the management of patients presenting with this toxicity, together with difficulties related to classifying ICI-CDI severity. Until now, specific guidelines on the management of ICI-CDI are lacking. Due to the rarity of ICI-CDI, endocrinological consultation may relieve medical oncologists from difficulties in treating this side-effect; oncologists, however, remain responsible for early diagnose of ICI-CDI and the management of ICIs as the causative drugs. To this aim, some practical suggestions are advised for the multidisciplinary management of cancer patients presenting with ICI-CDI.